Parlour games and the public life of women in Renaissance Italy - McClure, George W., 1951- (Toronto [Ont.] : University of Toronto Press, 2013)
Confined by behavioural norms and professional restrictions, women in Renaissance Italy found a welcome escape in an alternative world of play. This book examines the role of games of wit in the social and cultural experience of patrician women from the early sixteenth to the early eighteenth century.
The Renaissance Theory of Play -- The Academy of the Intronati and Sienese Women (1525-1555) -- The Games of Girolamo and Scipione Bargagli (1563-1569) -- Fortunes, Medals, Emblems : The Public Face of Private Women -- The Birth of the Assicurate: Italy's First Female Academy (1654-1704) -- Girolamo Gigli: The Legacy of the Sienese Games and Sienese Women.
Includes bibliographical references (pages 287-305) and index.
JSTOR
Keywords: Women -- Italy -- Social life and customs -- 16th century; Women -- Italy -- Intellectual life -- 16th century; Women -- Italy -- History -- Renaissance, 1450-1600.; Indoor games -- Social aspects -- Italy -- History -- 16th century; Renaissance -- Italy; Italy -- Social life and customs -- 16th century; Femmes -- Italie -- Mœurs et coutumes -- 16e siècle.; Femmes -- Italie -- Vie intellectuelle -- 16e siècle.; Femmes -- Italie -- Histoire -- 1450-1600 (Renaissance); Renaissance -- Italie; Italie -- Mœurs et coutumes -- 16e siècle.; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; HISTORY -- Renaissance; Manners and customs; Renaissance; Women -- Intellectual life; Women -- Renaissance; Women -- Social life and customs; Italy; 1450-1600; History